Mechanistic investigation of the carbon-iodine bond activation on the niobium-carbon cluster - Sengupta, Turbasu; Khan, Muntazir S.; Pal, Sourav (ACS Omega, 2017)
The activation process of carbon-iodine (C-I) bond on neutral and cationic niobium metcars (Nb8C12) is investigated using density functional theory and related computational techniques. Metallocarbohedrenes or metcars are a class of stable metal-carbide clusters of specific stoichiometry and of great interest to cluster chemists since their first discovery. The detailed reaction mechanism along with the overall energy profile of the C-I dissociation reaction on niobium metcar and its cations is presented in this paper. The tunneling-corrected rate constants and their related reaction parameters such as the pre-exponential factor are also included alongside. The major differences between the reaction mechanism of the neutral and cationic metcars are also highlighted as well. Despite the available experimental results, the C-I bond dissociation on metcars has remained an unexplored problem in the theoretical and computational domains. Thus, the present investigation can fill in the gap and may also provide new insights provoking further developments in cluster and materials chemistry in future.